2017
DOI: 10.1007/s00268-016-3859-5
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Assessment of Clinical and Patient‐Reported Outcomes of Initial Non‐Operative Management of Ventral Hernias

Abstract: While the short-term risk of emergency surgery with non-operative management of ventral hernias is moderate, the chance of an emergency room visit and surgery is high. Patients who undergo non-operative management of their ventral hernias have no change in patient-reported outcomes at one year, while those converted to operative management experience improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…9 Moreover, nonoperative management results in poor quality of life and functional status. 10,33 In a 2016 prospective, case-matched study 10 of operative vs nonoperative management of ventral hernia, operative management improved overall function and quality of life. Another prospective study from 2019 34 that compared long-term outcomes of operative vs nonoperative management found that this improvement was sustained 3 years after the surgical procedure and that nearly 40% of patients in the nonoperative group ultimately went on to undergo hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, nonoperative management results in poor quality of life and functional status. 10,33 In a 2016 prospective, case-matched study 10 of operative vs nonoperative management of ventral hernia, operative management improved overall function and quality of life. Another prospective study from 2019 34 that compared long-term outcomes of operative vs nonoperative management found that this improvement was sustained 3 years after the surgical procedure and that nearly 40% of patients in the nonoperative group ultimately went on to undergo hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…Data specifically on umbilical and epigastric hernias were not available. In a small prospective observational study 22 of 25 patients in whom non-operative treatment of a primary ventral hernia was planned, and who were followed for a median of 12 months, 20 and 4 per cent underwent elective and emergency repair respectively.…”
Section: Quality Of Evidence: Strength Of Recommendation: Weakmentioning
confidence: 99%
“…WW of ventral hernias is associated with a low risk of requiring emergency surgery (2.6% over one year) [ 12 ]. Overall, 16-23% of patients cross over, requiring surgical repair during relatively short follow-up periods of one to five years [ 13 , 14 ]. It has also been demonstrated that patients undergoing ventral hernia repair at index presentation had a statistically significant improvement in their quality of life compared to those who underwent WW [ 15 ].…”
Section: Discussionmentioning
confidence: 99%